Comparison of Postoperative Pain after using Passive Ultra Sonic Activation (PUA) and Manual Dynamic Agitation (MDA) during Root Canal Treatment - Abdullah, Ahmed; Syed Muzammil Hussain; Azeem, Shehroze; Khurshid, Talha; Naqvi, Syed Shan e Haider (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate post-treatment pain after using manual dynamic agitation and passive ultrasonic activation as final irrigation activation protocols in endodontic therapies. Study Design: Randomized Controlled Trial (clinicialtrials.gov: NCT05852444). Place and Duration of Study: Department of Operative Dentistry and Endodontics, Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from May to Nov 2023. Methodology: In total, 90 patients were randomly split into 2 Groups. In Group MDA, master GP cones were used for irrigant agitation while in Group PUA, an ultrasonic device (Ultra-X) was used. Pain at three different intervals (8h, 24h, and 48h) was evaluated using VAS and NSAIDs were prescribed for pain relief. Results: Pain scores differed substantially between the two Groups at 8, 24, and 48 hour time intervals (p<0.05). The Group PUA consistently showed a lower mean score at all three time intervals with the statistical analysis revealing significant differences in pain experience between Group PUA and Group MDA with a highly significant difference in pain distribution across all times. Conclusion: Manual irrigant agitation with gutta percha cones causes significantly more pain than passive ultrasonic activation.